Forbidden Four Cycle, Star Graphs and Isometric Embeddings - Dovgoshey, Oleksiy; Rovenska, Olga (Odesa National University of Technology, 2026)
We prove the necessary and sufficient conditions under which ultrametric spaces of arbitrary infinite cardinality admit isometric embeddings into ultrametric spaces generated by labeled star graphs.